The Meaning of Risk in Stock Investment: A Phenomenological Study of Beginner Investors - Retnowati Jasa; Bambang Sugeng Dwiyanto; Dian Widyantini; Wiwit Agustina; Dany Luqyana Idris (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the capital market in Indonesia has increased the number of novice investors investing in stocks through various digital platforms. However, this increased participation has not been fully accompanied by a deep understanding of investment risk. Most previous studies have focused on quantitative risk measurement, while the meaning of risk based on investors' lived experiences is still relatively rare. This study aims to understand the meaning of risk in stock investment from the perspective of novice investors using a phenomenological approach. This study employed a qualitative method with a phenomenological approach. Informants were selected through purposive sampling technique, namely novice investors who have actively invested in stocks, have experienced both profits and losses, and are willing to share their investment experiences. Data were collected through in-depth interviews, observation, and documentation, then analyzed using phenomenological analysis stages through bracketing, horizontalization, grouping themes, and compiling textural and structural descriptions to uncover the essence of informants' experiences. The results show that risk is interpreted as an integral part of stock investment, not simply the potential for financial loss. Experience with losses, market fluctuations, and emotional stress shapes investors' perspectives to become more rational, cautious, and able to control their emotions when making investment decisions. Furthermore, the social environment and digital media influence risk perception, although personal experience is a key factor in developing a more mature understanding. This research contributes to the development of behavioral finance studies by demonstrating that the meaning of risk is a construct of investors' lived experiences. The research findings also offer practical implications for regulators, securities firms, and educational institutions in designing investment education programs that emphasize risk understanding and managing investor behavior.